Causal effects of parents' education on children's education - John Ermisch; Chiara Pronzato (University of Essex, Institute for Social and Economic Research (ISER), 2010)
The paper shows that parents education is an important, but hardly exclusive part of the common family background that generates positive correlation between siblings educational attainments. Our estimates based on Norwegian twins indicate that an additional year of either mothers or fathers education increases their childrens education by as little as one-tenth of a year. There is evidence that fathers education has a larger effect than that of mothers: one explanation is that better educated mothers work more in paid employment and spend less time interacting with their children. We test this hypothesis and find no evidence to support it.
Keywords: C23; I2; 330; intergenerational transmission; education; mothers time; twin-estimator; sibling-estimator; Bildungsinvestition; Bildungsniveau; Eltern; Kinder; Norwegen